Pemberdayaan Masyarakat yang Tanggap dan Waspada di Masa Pandemi Covid-19 di Kecamatan Mayangan - Trismawati Trismawati; Adam Febrian Maulana (Abdi Panca Marga, 2021)
During the Covid-19 pandemic, the high rate of spread of the virus in the Probolinggo area disrupted stability in all aspects. Against this background, the Panca Marga University Community Service Program (Real Work Lecture) of the Mayangan sub-district group compiled a work program with a focus on gaining insight and preparedness about the dangers of transmission of the Covid-19 virus which was implemented through 5M counseling activities, distribution of masks and hand sanitizers, planting. TOGA (Family Medicinal Plants), spraying disinfectant at public facilities and manufacturing starfruit juice products. The result of the activity was an increase in the insight and alertness of the people of Mayangan sub-district about the dangers of transmission of the Covid-19 virus and how to prevent it. The conclusion of this community service activity carried out in the Mayangan sub-district is the need for counseling and socialization about the spread of the Covid-19 virus in any community because the Covid-19 virus infection can attack anyone.